THE CREATION OF “LA VALSE” BY MAURICE RAVEL AND THE STUDIES ON IT IN CHINA AND THE WEST - Xiaoyu, Li (E-Journal VFU, 2025)
La valse is a symphonic dance poem by French composer Maurice Ravel, originally conceived as a ballet but subsequently developed into several versions. This article presents the context of the work's creation, the evolution of the genre, and the different versions of the adaptation, as well as examining the differences in Chinese and Western scholars' research regarding the performance practice, musical language, and cultural content of the work.
Keywords: Ravel; "La valse"; comparison between Chinese and Western studies